MULTISTATIC SONAR OPERATOR VISUALIZATION DEVELOPMENT REQUIREMENTS - Gammon, Mark A.; Strode, Christopher (Canadian Acoustics, 2015)
The operational community has been using multistatic sonar for numerous years yet the development of applications for operator visualization of multistatic sonar performance is lacking. Such applications may enhance the operator’s ability to visualize the multistatic sonar’s real time performance to optimize sensor employment. One of the key issues is the transition from legacy sonar monostatic performance acoustic prediction to multistatic sonar acoustic prediction. While many such applications have been developed, the majority of these pertain to the analysis of multistatic sonar and not the direct operator visualization of that performance. In order to be able to provide a completely effective system from the standpoint of both sensors and users, this challenge must be addressed. One of the key parameters is the ocean environment, in particular realistic modelling for the purpose of sonar performance prediction, yet numerous other factors will influence actual operations. Techniques have recently been field tested to provide the operator with Operational Analysis (OA) tools and advice, and further work in the area of near-real time Operator Visualization Development (OVD) is essential. A system engineering approach advocates an integrated system to provide the near-real time sonar performance prediction embedded in the sonar display. Such a system does not and will probably never fully allay the acoustic performance prediction problem given the uncertainty in acoustic analysis. However it must provide useful system performance information to the operator in order to optimize sensor employment. Hence, a new conceptual framework is required for Multistatic Sonar OVD (MSOVD).